Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The Extent to which Public School’s Principals’ in the Directorate of Ramallah and Al-Bireh Practice and Manage Change within a Conversational Culture from the Teachers’ Point of ViewCo-Prof. Sahar Said Marbou, Asst-Prof. Nabil Suleiman Rummaneh2. The role of a university professor in developing core values and promoting positive behavior of applied accounting students at King Khalid University and its obstacles from the professors' point of viewDr. Mona Abdelrhman Yagoub3. Assessing the Practices of Computer Teachers in Light of the Requirements of Formative Evaluation Strategies at the Intermediate Stage in the Kingdom of Saudi ArabiaMr. Abdu Abdullah Saeed Alshaikhi, Dr. Abdulelah Hamoud Alshehri4. Patterns of Family Upbringing and its Relationship to Perfectionism among Talented Students in Qassim RegionProf. Eltayb Mohammed Z. Yousef, Mr. Nasser Khalaf A. Almutairi5. The Effectiveness of a Program Based on Interactive Theater in Developing Some Behavioral Etiquette in Early ChildhoodMrs. Amjad Ahmed Al-Zahrani6. Reality of using electronic activities in educational process from the perspective of schools principals in educational directorate of Ramallah and Al-BirehMrs. Noor Anees Karzoun7. The reality of the technical skills necessary to carry out scientific research among the trainees of the Technical College for Girls in Tabuk, Saudi ArabiaMrs. Fatimah Salem Alamrani, Dr. Ameera Maitiq Aljuhani, Mrs. Amal Ahmed Asiri8. The reality of technology valleys as a policy for financing Saudi universities and their activation proposals in the light of the American Silicon Valley experienceMrs. Ameena Ali Sanior
Keywords: Journal of Educational and Psychological Sciences